Edward Jenner and the Small Pox Vaccine - Smith, Kendall A. (Frontiers in Immunology, 2011)
Edward Jenner, who discovered that it is possible to vaccinate against Small Pox using material from Cow Pox, is rightly the man who started the science of immunology. However, over the passage of time many of the details surrounding his astounding discovery have been lost or forgotten. Also, the environment within which Jenner worked as a physician in the countryside, and the state of the art of medicine and society are difficult to appreciate today. It is important to recall that people were still being bled at the time, to relieve the presence of evil humors. Accordingly, this review details Jenner’s discovery and attempts to place it in historical context. Also, the vaccine that Jenner used, which decreased the prevelance of Small Pox worldwide in his own time, and later was used to eradicate Small Pox altogether, is discussed in light of recent data.